COVID 19 Emergency Policy Responses : Why Credit Reporting Matters in the Stabilization and Recovery Phases? - Masunda, Collen; Sankaranarayanan, Shalini; Chhabra, Pratibha; Fraboni, Fabrizio; Salamina, Luz Maria (World Bank, Washington, DC, 2020)
Firms and individual borrowers are experiencing a sharp decrease in income due to COVID-19 (coronavirus), making them unable to meet their credit obligations. Governments, Central Banks and financial sector regulators across the globe have proactively intervened to support the credit markets and avert a possible credit freeze by introducing unprecedented measures such as regulatory forbearance (includes moratoria on repayments, extension of past-due days). Given the interplay between fiscal, monetary and prudential policies, there is need for a coordinated and holistic approach to policy formulation and implementation to increase the likelihood of success of these measures in the longer term. For example, it is important that measures be carefully implemented, mindful of the implications on the credit information cycle because inaccurate and untimely data may delay recovery from the crisis. Properly functioning credit reporting systems can assist in the stabilization and recovery phases through supporting private sector credit granting, minimizing cost of public intervention, data driven policy formulation, credit classifications and IFRS 9 ECL computations.